Treatment with lenalidomide induces immunoactivating and counter-regulatory immunosuppressive changes in myeloma patients. (9th July 2014) - Busch, A; Zeh, D; Janzen, V; Mügge, L-O; Wolf, D; Fingerhut, L; Hahn-Ast, C; Maurer, O; Brossart, P; von Lilienfeld-Toal, M
Summary: Lenalidomide activates the immune system, but the exact immunomodulatory mechanisms of lenalidomide in vivo are poorly defined. In an observational study we assessed the impact of lenalidomide on different populations of immune cells in multiple myeloma patients. Lenalidomide therapy was associated with increased amounts of a CD8 + T cell subset, phenotypically staged between classical central memory T cells (TCM) and effector memory T cells (TEM), consequently termed TCM/TEM. The moderate expression of perforin/granzyme and phenotypical profile of these cells identifies them as not yet terminally differentiated, which makes them promising candidates for the anti-tumour response. In addition, lenalidomide-treated patients showed higher abundance of CD14 + myeloid cells co-expressing CD15. This population was able to inhibit both CD4 + and CD8 + T cell proliferation in vitro and could thus be defined as a so far undescribed novel myeloid-derived suppressor cell (MDSC) subtype. We observed a striking correlation between levels of TCM/TEM, mature regulatory T cells (Tregs ) and CD14 + CD15 + MDSCs. In summary, lenalidomide induces both activating and inhibitory components of the immune system, indicating the existence of potential counter-regulatory mechanisms. These findings provide new insights into the immunomodulatory action of lenalidomide.